Dynamic studies and controller design for acid and base pH neutralization process / \c Muhammad Ghazali Othman - Muhammad Ghazali Othman (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
In this history of human development over time, man has affected the natural ecosystems in various ways. During these modern days much of the efforts of environmental restoration, concentrate on new sources for clean energy, transportation and to larger extent, wastewater treatment. Since the quality standards for Wastewater Treatment Plants (WWTPs) become more stringent , efficient control management methods and procedures are therefore crucial to be implemented for economic and environmental reasons. The pH neutralization process is one of the several methods adopted by environmental managers in the business of wastewater treatment especially in the developed countries.